2019
DOI: 10.5694/mja2.50315
|View full text |Cite
|
Sign up to set email alerts
|

Residual risk of infection with blood‐borne viruses in potential organ donors at increased risk of infection: systematic review and meta‐analysis

Abstract: Objective To estimate the prevalence and incidence of human immunodeficiency virus (HIV), hepatitis C virus (HCV), and hepatitis B virus (HBV) among people at increased risk of infection in Australia; to estimate the residual risk of infection among potential solid organ donors in these groups when their antibody and nucleic acid test results are negative. Study design Systematic review and meta‐analysis of reports of the incidence and prevalence of HIV, HCV, and HBV in groups at increased risk of infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…Possible sources of viral infection recognized post transplant include re‐activated latent infection, 37 or newly acquired infection. Risk of unrecognized donor window‐period infection is very low 38 . Concerns from a biovigilance perspective about high rates of new virus notifications include the possibility of further late‐detected transmissions, particularly the 16 recipients from donors with viral infections who developed the same de novo infection more than 12 months after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Possible sources of viral infection recognized post transplant include re‐activated latent infection, 37 or newly acquired infection. Risk of unrecognized donor window‐period infection is very low 38 . Concerns from a biovigilance perspective about high rates of new virus notifications include the possibility of further late‐detected transmissions, particularly the 16 recipients from donors with viral infections who developed the same de novo infection more than 12 months after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…These data are reassuring, as they confirm the renewed screening program is performing as expected. Organs are often rejected for transplantation if potential donors are at increased risk of blood‐borne virus infections, including men who have sex with men, injecting drug users, sex workers, and prisoners. Waller and her colleagues undertook a rigorous systematic review and meta‐analysis to estimate the residual risk in Australia of infection with human immunodeficiency virus (HIV) or hepatitis C (HCV) or B viruses (HBV) by organ donors from groups at increased risk who have negative viral test results. They found that the absolute residual risks of infection were very low, and that judicious acceptance of organs from such donors could reduce transplant waitlist mortality by providing organs for as many as 30 additional recipients each year in NSW alone. The Getting it Right Collaborative Group undertook an important validation study of a culturally adapted version of the nine‐item Patient Health Questionnaire (aPHQ‐9) as a screening tool for depression in Indigenous Australians.…”
Section: Articles Short‐listed For the Mja Mda National Prize For Exmentioning
confidence: 99%
“…4 During the "serological window period," the blood and/or the donor organ can have the virus present with a negative serology, and can transmit the infection to the recipient. 8 This phenomenon led to the use of nucleic acid testing (NAT).…”
Section: Introductionmentioning
confidence: 99%